2019
DOI: 10.21608/eajbsh.2019.44518
|View full text |Cite
|
Sign up to set email alerts
|

Response of Wheat Plants to Seaweed Extracts and Fluvic Acid under Irrigation with Drainage Water

Abstract: Two field experiments were conducted at the Rosetta region, El_Behira Governorate, Egypt, during 2017/2018 and 2018/2019 growing seasons to study the effect of water quality, fulvic acid and seaweed extracts on the yield, its components and quality characters of wheat plant (Giza 168), in split-split plot design with three replications. The main plots included irrigation water quality (Nile water and Agricultural drainage water), while seaweed extracts (control, 50 and 100 g SW/fed) was arranged in the subplot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
3
0
0
Order By: Relevance
“…ha -1 ,The reason for this is due to the role of physiological stimulants and growth regulators such as gibberellin and auxin, which led to cell divisions and elongation in the vegetative parts, especially in the elongation stage. These results are consistent with the findings of [46,52] ,who reported that seaweed extract increases biological yield, and this was confirmed by [49,53], showed that the components of marine algae extract such as micro-nutrients, amino acids, vitamins, cytokinins, auxin and abscisic acid increase growth and thus raise the efficiency of cellular metabolism in treated plants that leads to an improvement in biological yield .As for the interaction between planting dates and treatments of spraying with physiological stimulant between Table 9, there were significant differences, as the data recorded the highest biological yield when treating spraying with physiological stimulant at the stage of elongation and booting at the first date amounted to 11.46 tons. ha -1 ,The lowest biological yield was recorded when the plants were not treated with the physiological stimulant at the second date, which amounted to 9.84 tons.…”
Section: Biological Yield (Tons Ha -1 )supporting
confidence: 93%
See 1 more Smart Citation
“…ha -1 ,The reason for this is due to the role of physiological stimulants and growth regulators such as gibberellin and auxin, which led to cell divisions and elongation in the vegetative parts, especially in the elongation stage. These results are consistent with the findings of [46,52] ,who reported that seaweed extract increases biological yield, and this was confirmed by [49,53], showed that the components of marine algae extract such as micro-nutrients, amino acids, vitamins, cytokinins, auxin and abscisic acid increase growth and thus raise the efficiency of cellular metabolism in treated plants that leads to an improvement in biological yield .As for the interaction between planting dates and treatments of spraying with physiological stimulant between Table 9, there were significant differences, as the data recorded the highest biological yield when treating spraying with physiological stimulant at the stage of elongation and booting at the first date amounted to 11.46 tons. ha -1 ,The lowest biological yield was recorded when the plants were not treated with the physiological stimulant at the second date, which amounted to 9.84 tons.…”
Section: Biological Yield (Tons Ha -1 )supporting
confidence: 93%
“…m -2 They were compared with the treatment without spraying, as the average number of spikes per unit area in this treatment was 335 spikes. m -2 , The reason for the increase in the number of spikes per unit area at this stage is due to the efficiency of the physiological stimulant in the process of regulating and balancing growth in all parts of the plant, including the straws, because the stimulant contains growth regulators, which also contributed to an increase in chlorophyll and photosynthesis processes, and this is consistent with [45][46][47], who indicated the importance of algae extract in stimulating plant growth and photosynthesis through its content of growth regulators, amino acids and some micro-nutrients, The results of Table 7 showed that the overlap between planting dates and spraying stages is significant, as the results recorded an increase in the number of spikes per unit area when planting on 15/11 and the plants were treated by spraying on the leaves at the two stages of tillering and elongation amounted to 381 spikes. When planting on 15/12, the number of spikes per unit area was 326 spikes.m -2 .The physiological stimulant enhanced the increase in the number of spikes per unit area, in addition to the availability of appropriate climatic conditions on the first date.…”
Section: The Number Of Spikes Per Unit Area (Spike M -2 )supporting
confidence: 84%
“…m -2 ,The reason for the increase in the number of spikes per unit area at IOP Publishing doi:10.1088/1755-1315/1158/6/062021 12 this stage is due to the efficiency of the physiological stimulant in the process of regulating and balancing growth in all parts of the plant, including the straws because the stimulant contains growth regulators, which also contributed to an increase in chlorophyll and photosynthesis processes. This is in agreement with [38,65,66], who pointed out the importance of seaweed extract in stimulating plant growth and photosynthesis through its content of growth regulators, amino acids and some micronutrients. The results of Table 10 showed that the interaction between planting dates and spraying stages is significant, as the results recorded an increase in the number of spikes per unit area when planting on the date of 15/11, and the plants were treated by spraying on the leaves at the stages of tillering and elongation, which amounted to 381 spikes.…”
Section: The Number Of Grains In the Spike ( 1 Grain Spike -1 )supporting
confidence: 91%